Social humanism : a new metaphysics - Ellis, B. D. (Brian David), 1929- (Routledge studies in ethics and moral theory, 2012)
"In this book, Ellis argues that moral and political objectives are not independent of one other, and so must be pursued in tandem. Social humanism is a moral and political philosophy that does just this. As a political philosophy, it justifies the implementation and maintenance of many of the characteristic social policies of welfare states. As a moral philosophy, it provides the foundation required for most human rights legislation. To this end, Ellis elaborates on the theory of social humanism and the need to reconsider the metaphysical foundations of morals. He develops the theory of social idealism as a meta-theory for both morals and social policy, exploring the global consequences of this new approach."--Publisher's website.